Membangun Politik Pengakuan Pada Masyarakat Multikultural (Studi Pada Desa Sumber Mulyo Kecamatan Muara Sugihan Kabupaten Banyuasin) - Riyana, Riyana Marfungah; Marfungah, Riyana; Apriani, Reni (Jurnal Studi Ilmu Politik, 2024)
Building a politics of recognition in a multicultural society. This research was conducted in Sumber Mulyo Village, Muara Sugihan District, Banyuasin Regency and used social identity theory from Henri Tajfel in Hogg's identity theory which stated that there are three reasons for building a politics of recognition, namely, self-categorization, social comparison and interactional models. This type of research uses descriptive qualitative. The data collection method for this research is through interviews and documentation. The results of this research show that there are three reasons for building a politics of recognition, namely, self-categorization by attracting public interest through promising work programs, especially among farmers and youth, social comparison carried out by following the customs and customs of the Javanese people and interactional models by studying and mastering the culture of Javanese society to gain political recognition from the majority ethnic community. Two factors influence the victory of a village head candidate from an ethnic minority to gain recognition from the community. The first is the structural factor of the winning team. Second, the influence factor of the individual history of the village head candidate shows that the community is starting to think about electing a village head candidate from an ethnic minority and a politics of recognition is being formed among the people of Sumber Mulyo Village, Muara Sugihan District, Bnyuasin Regency.